Functional characterization of interferon regulatory factor 5 and its role in the innate antiviral immune response. Issue 72 (January 2018) - Ai, Kete; Luo, Kai; Xia, Lihai; Gao, Weihua; Hu, Wei; Qi, Zhitao; Xu, Qiaoqing
Abstract: In mammals, type I interferons (IFNs) are primarily regulated by transcription factors of the IFN regulatory (IRF) family. Interferon regulatory factor 5 (IRF-5) plays pivotal roles in antiviral and inflammatory responses. In the present study, we found that zebrafish ( Danio rerio ) IRF5 is a key player in the regulation of the expression of type I IFN and its antiviral immune response. IRF5 was upregulated in zebrafish embryonic fibroblast cells (ZF4) when challenged with grass carp reovirus (GCRV). Moreover, the expression profiles of Mx, IFN, Viperin, and IRF7, but not IRF3, were upregulated by overexpression of IRF5 in Epithelioma papulosum cyprinid cells (EPCs). Luciferase assays revealed that the activation of the IFNϕ1 promoter was stimulated by overexpression of IRF5 and IRF5-△IAD (IRF5 lacking the IRF-associated domain), respectively. However, overexpression of IRF5 or IRF5-△IAD inhibited the activity of the IFNϕ3 promoter. IRF5-△DBD (lacking the DNA-binding domain) had no influence in the activation of the IFNϕ1 and IFNϕ3 promoters. Furthermore, the determination of the cytopathic effect (CPE) numbers and viral titers revealed that the viral concentration was reduced by ectopic expression of IRF5 in EPC cells. Ectopic expression of IRF5 in EPC cells could protect cells from GCRV and significantly inhibited GCRV virus replication. These data indicated that IRF5 could limit viral replication through an IFN-dependent pathway. Highlights: The manuscript first investigated the function of zebrafish IRF5. Zebrafish IRF5 could act as both an activator and a repressor of IFN gene induction. Ectopic expression of IRF5 in EPC cells could protect cells from GCRV and significantly inhibited GCRV virus replication.